Comparative toxicity of spinetoram to Trialeurodes vaporariorum Westwood and its parasitoid Encarsia formosa Gahan - Drobnjaković, Tanja; Prijović, Mirjana; Porcu, Emanuele; Ricupero, Michele; Siscaro, Gaetano; Zappalà, Lucia; Biondi, Antonio (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2023)
The role of selective new generation bionsecticides, beside their effectiveness against key pests, relies on their safety to beneficial arthropods. Spinetoram, a semi-synthetic analogue of the microbial-derived bioinsecticide spinosad is registered worldwide for application to numerous crops, but its ecotoxicological risk assessment to beneficial arthropods has hardly been documented. Moreover, this is the first report regarding the toxic effects of spinetoram on a pest- the greenhouse whitefly Trialeurodes vaporariorum Westwood (Hemiptera: Aleyrodidae), and/or its successful biocontrol agent, parasitoid Encarsia formosa Gahan (Hymenoptera: Aphelinidae). In laboratory conditions we assessed the acute toxicity of spinetoram insecticide (25% a.i.) to adults, nymphs and eggs of the greenhouse whitefly, as well as to adult and pupal stage of the parasitoid. In all concentration-response bioassays, the spinetoram insecticide was applied to tobacco leaves settled onto 1% agar layer in ventilated Petri dishes using a Potter spray tower. The acute toxicity parameters of spinetoram on adults of both pest and parasitoid were evaluated in residual contact bioassays, while whitefly eggs and nymphs, and pupae of the parasitoid were topically treated with a series of spinetoram concentrations, covering a range of 10-90% mortality. The lethal effects of spinetoram on parasitoid E. formosa was assessed through Selectivity ratio (SR) estimations, showing the ratios beetween median Lethal Concentrations (LC50s) estimated for the parasitoid, compared to LC50s estimated for the pest. The following LC50 values were evaluated: 4.593, 15.027 and 11.73 mg a.i./l for whitefly adults, nymphs and eggs, respectively, and 0.686 and 1.715 mg a.i./l for parasitoid adults and pupae, respectively. The calculated SR estimations were less than 1, indicating that spinetoram insecticide is non-selective towards the both tested stages of the parasitoid E. formosa. A more complete understanding of spinetoram impact on E. formosa within whitefly integrated management requires further evaluation of the sublethal effects and greenhouse trials, with an emphasis on population-level responses.
Keywords: bioinsecticide; Encarsia formosa; IPM; selectivity ratio; whitefly